2016
DOI: 10.18632/oncotarget.7664
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 3 promotes the stem-like properties of gastric cancer cells via Wnt/GSK-3β/β-catenin pathway

Abstract: Cancer stem cells (CSCs) are believed to contribute to the tumor growth in gastric carcinoma (GC), a common lethal malignancy. This study investigated the effect of aquaporin 3 (AQP3) on stem-like properties of human GC cells. Elevated AQP3 expression was associated with CD44 expression in human GC specimens. Expression of AQP3 and that of CD44 positively correlated with Lauren classification, lymph node metastasis, and lymphovascular invasion. Altering the AQP3 expression had pronounced effects on the tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Recently, it has been shown that AQP3 expression might be related to development of several carcinomas including gastric carcinoma [26,27], oesophageal and oral squamous cell carcinoma [28], cervical carcinoma [29] and cancers of the thyroid [30], pancreas [31], prostate [32,33], ovary [34] and skin [35,36]. In our study, AQP3 expression was observed in all tissue samples examined in LMS group except in one case.…”
Section: Resultssupporting
confidence: 62%
“…Recently, it has been shown that AQP3 expression might be related to development of several carcinomas including gastric carcinoma [26,27], oesophageal and oral squamous cell carcinoma [28], cervical carcinoma [29] and cancers of the thyroid [30], pancreas [31], prostate [32,33], ovary [34] and skin [35,36]. In our study, AQP3 expression was observed in all tissue samples examined in LMS group except in one case.…”
Section: Resultssupporting
confidence: 62%
“…To investigate the effects of AQP3 on chemosensitivity in GC cells, its expression was upregulated in AGS cells and downregulated in MGC803 and SGC7901 cells by lentiviral transduction, as previously reported (Figure 1b). 12,13 AQP3 overexpression induced cDDP resistance compared with control AGS cells ( P <0.05, Figure 1c), and AQP3 knockdown increased the chemosensitivity of MGC803 and SGC7901 cells ( P <0.05, Figure 1c). Furthermore, AQP3 expression in MGC803, SGC7901 and AGS cells was significantly enhanced after cDDP treatment respectively (Figure 1d).…”
Section: Resultsmentioning
confidence: 96%
“…Immunofluorescence was conducted according to the methods reported by Zhou et al 13 A primary antibody against LC3 A/B (Cell Signaling Technology, Beverly, MA, USA) was used. The secondary antibody was obtained from Beyotime (Beyotime Institute of Biotechnology, Henan, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP3 can transport glycerol across the cytomembrane7 and is involved in the regulation of cell proliferation and migration in both normal and tumor tissues 2,10,37,38. Overexpression of AQP3 has been reported in diverse tumors, including GC,39 colorectal cancer,40 lung carcinoma41 and esophageal and oral squamous cell carcinoma 9.…”
Section: Discussionmentioning
confidence: 99%